Simulating urban evolution by H-GIS and H-BIM: a temporal and spatial study of Pingjiang map - Pania Yanjie Mu; Sarah E. Fraser; Maolin Peng (Heritage Science)
Abstract Historical maps provide insights into the morphology, cultural, and political shifts of ancient societies. Pingjiang Map is one of the earliest comprehensive ancient Chinese maps, depicting the heritage water city of Suzhou. This study takes it as the subject to examine the temporal and spatial reconstructions of Suzhou city after its devastation in the Song-Jin wars during the twelfth–thirteenth centuries. It uses historical geographical information system (H-GIS) and historical building information management (H-BIM) to simulate Suzhou city in the Southern Song dynasty (1127–1279) and the city’s subsequent modernization to the present. By comparing and contrasting Pingjiang Map, the Song dynasty Suzhou, and the current city in the configuration of clusters such as urban wall, canal, street, government and citadel, temple, and residential ward, we establish evolutionary links between Pingjiang Map and the city, providing insights to the mechanism underlying urban transformation. Through H-BIM, we conducted a temporal and spatial analysis of the twelfth–thirteenth centuries’ citadel of Suzhou, simulating the construction sequence of palatial artefacts. Our research argues that Pingjiang Map stele forged an imperial vision, serving both for documentation and planning. It encoded building information for the central government to manage post-war reconstruction. The research establishes the workflow of ‘SQS’—spatialization, quantitative analysis, and simulation—to investigate the evolution of imperial cities and their cartography.